An assessment of residence and influence times in Xiamen Bay, China. (5th November 2021) - Cheng, Peng; Wang, Aijun; Wu, Jiezhong; Lin, Yihui; Chen, Jixin; Chen, Nengwang
Abstract: Water transport time scales are important indicators to assess the renewal of substance inside coastal embayments. Estimates of water renewal efficiency represented by residence and influence times in Xiamen Bay were made via a series of numerical experiments, using the instantaneous tracer injection method. It was found that the average e -folding threshold residence time in the bay is approximately 16.5 days, and that the residence time increases near the entrances to land because water exchange between the bay and the Taiwan Strait is the dominant water-renewal process. The seawater influence time has a similar spatial distribution to the residence time. The freshwater influence time is much shorter in the western region of the bay than in the eastern region, which shows that the influence of Jiulong River freshwater is largely restricted to the western region. The changes in the residence and influence times reveal that increased river discharge mainly accelerates water renewal in the western region of the bay, whereas increased tides mainly accelerate water renewal in the eastern region and the northern part of the western region. The drivers of water renewal were examined using effective transport velocities that were defined based on the decomposition of tracer flux, and showed that tidal residual flow determines the extent of water renewal in Xiamen Bay. The estimation of residence time is sensitive to the operation of instantaneous method. The release of tracer at spring tide results in a shorter residence time and the use of a small threshold can improve the consistency of estimated threshold residence times. Highlights: Residence time is 16.5 days over Xiamen Bay and increases from entrances to land. Seawater influence time has a similar distribution to that of residence time. Freshwater influence time is shorter in the western region than in the eastern region. Increasing river discharge mainly accelerates water renewal in the western region. Increasing tides mainly accelerate water renewal in the eastern region.